Experimental process design for sorption capacity of Kogi and Ibusa clay activated with HNO3 and H2SO4 acids in palm oil bleaching. (1st January 2014) - Uzoh, Chigozie Francolins; Onukwuli, Okey D.; Nwabanne, Joseph Tagbo; Igbokwe, Philo P.K.
The palm oil bleaching process was optimised through characteristic study of the sorption capacity of Ibusa and Kogi clay activated with nitric and sulphuric acids. The raw clays were characterised for structure elucidation via FTIR and X-ray fluorescence spectroscopic techniques and the result indicates that Kogi clay is predominantly kaolinite while Ibusa sample is montmorillonite. The response surface methodology based on 4 2 - full factorial design was applied for the process analysis. Effects of process variables such as acid concentration, bleaching temperature, contact time, clay-oil ratio and particle size distribution was analysed employing the characterisation-control-optimisation paradigm necessary for detailed process design for optimum bleaching efficiency. A sequence of experiments was carried out at different settings of the process variables and their interactive sorption effects were calculated in terms of adsorption efficiency. Acid concentration and bleaching time were found to be the most significant process parameter. Predictive equations describing the optimum bleaching efficiency in terms of the process variables were derived from regression analysis of the experimental data. A maximum mean adsorption strength of 40 units was predicted for both specimens through activation wit HNO 3 acid at mean acid concentration of 6.12 mol/l and mean bleaching time of 48.88 mins, while H 2 SO 4 acid recorded relatively low adsorption strength of 24 units with Kogi clay and negligible strength of 8 units with Ibusa sample at the same experimental condition. Overall, HNO 3 acid activated Kogi clay shows robustness to expanded variable effects and could be recommended for general application in lieu of bentonite.